Penerapan Metode Thurstone dalam Mengukur Kualitas Instrumen dan Membuat Usulan Instrumen Tes Potensi Akademik (TPA) - Diana Suzana Mandar (Universitas Bunda Mulia, 2017)
Instrument is one of device that can be used as a tool to measure an object or collect data about a variable data collected through a particular instrument can then be described and attached to or used to test the hypothesis. In this study, these instrumen develop to meet the academic requirements to pass the higher education level. The data use in this study design by the available instrument and can also use as a self-made instrument. Instrument that has been available in general is already considered standard instrument to collect data specific variables. We can adjust the basis of the theory by using a standard instrument. In addition, the construct variables measured in the instrument must be in accordance with variable measuring. But if the standard instrument is not available, then the instrument must be develop by the researcher. Research instrument can be used to measure a variety of purposes both in nature and non-test test. The test is defined as the tools used to measure the knowledge or mastery of a set of measuring object and the content of certain materials. While non-test is a tool used to observe the phenomenon that is done through observation.Keywords: Metode Thurstone, Tes Potensi Akademik, Validitas Butir